MODEL KEBIJAKAN PENDAMPINGAN DAN PEMBERDAYAAN NELAYAN DALAM PENINGKATAN KESEJAHTERAAN EKONOMI - Sarjito, Aris (Universitas Panca Marga, 2024)
ABSTRACT This research delves into Indonesian fishermen's multifaceted challenges in sustaining their economic well-being, exploring policy interventions as a viable solution. Against a rapidly changing fishing industry and environmental pressures, the study aims to develop a comprehensive policy model to assist and empower fishermen. Using qualitative research methods, the investigation employs secondary data analysis to understand the socio-economic dynamics and identify key issues affecting the fishing communities. The findings highlight the urgent need for policy interventions that integrate social support mechanisms, ensuring a holistic approach to enhance the well-being of fishing communities. Strategies for promoting sustainable fisheries management within policy models emerge as crucial for long-term success. The research culminates in developing a robust policy model designed to foster sustainable fisheries and uplift the economic welfare of Indonesian fishermen. In conclusion, the practical application of the policy model emerges as a transformative tool for enhancing the economic welfare of Indonesian fishermen. The study contributes valuable insights for policymakers, stakeholders, and researchers interested in the intersection of sustainable fisheries management, community well-being, and effective policy design. Keywords: economic welfare, empowerment, fishermen, policy model